Inflation a risk in Bolivia: in the face of natural gas and NIR deaccumulation and the vulnerability of foreign debt and fiscal deficit - Vargas Díaz, César (2023)
The objective of this article is to provide an overview of the economic, social, community and productive model of Bolivia from 2006 to 2022, the model seeks mainly to maintain stable prices, i.e. low inflation with a control on domestic prices through the fixed exchange rate and international prices with fuel subsidies that are affected by the price of oil. All this, supported by the macroeconomic variables that we will study, such as the collapse of foreign currency income or dollars through the export of natural gas and savings from the deaccumulation of gold, foreign currency and special drawing rights, as well as the increase in spending on foreign debt, public spending in the state apparatus with fiscal deficit levels and subsidies for imports of diesel and gasoline fuels especially, each of these variables affected the country's savings through the net international reserves, as reflected in historical data. In addition, Bolivia is characterized by not promoting research, development, technology and innovation, knowledge with qualified human capital and productivity, which resulted in a high level of informal labor and unemployment, with insufficient productive sustainability in foreign currency dollars, affecting public policy issues in the short, medium and long term in the GDP.